Biofertilizer - Raja Abdul Rahman, Raja Noor Zaliha (2012)
The present invention relates to a biofertilizer comprising at least one bacterial strain selected from the group comprising Pseadomonas aeruginosa strain AGKT 1, Serratia marcescens strain AGKT4 and Bacillus amyloliquefaciens, and optionally also a suitable culture medium. The biofertilizer may further comprise a carrier, which is selected from cocoa pod husk, cocoa bean shell and peat moss. The biofertilizer may be used in combination with an NKP fertilizer.